2020
DOI: 10.1155/2020/6484129
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Evaluation through Machine Learning and a Global Fatigue Descriptor

Abstract: Research in physiology and sports science has shown that fatigue, a complex psychophysiological phenomenon, has a relevant impact in performance and in the correct functioning of our motricity system, potentially being a cause of damage to the human organism. Fatigue can be seen as a subjective or objective phenomenon. Subjective fatigue corresponds to a mental and cognitive event, while fatigue referred as objective is a physical phenomenon. Despite the fact that subjective fatigue is often undervalued, only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…In addition, frequent episodes of acute mental fatigue may increase the risk of developing more chronic forms of fatigue. For these reasons, many technical systems and analytic approaches have been developed to monitor the physiological manifestations of mental fatigue including plenty of studies that suggest that HRV may be particularly suited as a marker of fatigue [ 75 – 78 ]. The current study contributes to this field by suggesting that among the many HRV components, it may especially be the vagal-mediated components of the HRV spectrum that are reliable physiological indicators of operators’ fatigue in different work context.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, frequent episodes of acute mental fatigue may increase the risk of developing more chronic forms of fatigue. For these reasons, many technical systems and analytic approaches have been developed to monitor the physiological manifestations of mental fatigue including plenty of studies that suggest that HRV may be particularly suited as a marker of fatigue [ 75 – 78 ]. The current study contributes to this field by suggesting that among the many HRV components, it may especially be the vagal-mediated components of the HRV spectrum that are reliable physiological indicators of operators’ fatigue in different work context.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, recent developments in computer vision have been employed for player tracking (Bialkowski et al, 2015;Gade & Moeslund, 2018;Liu, Carr, Collins, & Liu, 2013;Lu, Ting, Little, & Murphy, 2013), pose estimation (Bridgeman, Volino, Guillemaut, & Hilton, 2019;Fastovets, Guillemaut, & Hilton, 2013;Sypetkowski, Kurzejamski, & Sarwas, 2019;Sypetkowski, Sarwas, & Trzcinski, 2019;F. Zhang, Zhu, & Ye, 2019), and automated injury prediction (Kampakis, 2016) based on, e.g., gait and fatigue analysis (Bartlett, 2006;Claudino et al, 2019;Kakavas, Malliaropoulos, Pruna, & Maffulli, 2019;Op De Beéck, Meert, Schütte, Vanwanseele, & Davis, 2018;Ramos et al, 2020).…”
Section: Event Detectionmentioning
confidence: 99%
“…Their findings showed that kinematic changes were related to fatigue for all runners, and fatigue was dependent on participants’ running technique [ 20 ]. To date, there are only a few studies focusing on continuous movement changes induced by fatigue, e.g., [ 1 , 20 , 21 ]. Ramos et al presented a machine learning system to evaluate fatigue using electromyographic (EMG) and heart rate variability (HRV) measurements [ 21 ].…”
Section: Related Workmentioning
confidence: 99%
“…To date, there are only a few studies focusing on continuous movement changes induced by fatigue, e.g., [ 1 , 20 , 21 ]. Ramos et al presented a machine learning system to evaluate fatigue using electromyographic (EMG) and heart rate variability (HRV) measurements [ 21 ]. The approach showed a potential to implement a combination of a dimensionless (0–1) global fatigue descriptor to reflect the onset of fatigue.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation